HEROIC NARRATIVES IN THE WORKS OF BA JIN AND BAURZHAN MOMYSHULY (Journal of Oriental Studies, 2025)
The article presents a comparative analysis of heroic narratives in the works of Chinese writer Ba Jin and Kazakh author Baurzhan Momyshuly, using narratological and ethical criticism theories. The study explores the authors’ perspectives, character systems, narrative forms, and artistic techniques in depicting the theme of war. The concept of heroism is revealed not only through acts of bravery on the battlefield but also through the character’s spiritual growth, inner transformation, and moral choices. In Ba Jin’s prose, heroism is portrayed within the framework of socialist realism, emphasizing the image of a collective hero, with patriotism depicted as an ideological duty. In contrast, Baurzhan Momyshuly's works foreground the inner discipline, willpower, and spiritual development of the heroic individual, closely tied to the writer’s military and pedagogical background.The study analyzes the narrative structures, systems of symbols and metaphors used by the authors, examining how national historical memory and cultural values are artistically represented. A comparative approach reveals how the concept of heroism emerges at the intersection of national identity and universal values in Chinese and Kazakh literature. The article offers a scholarly interpretation of the transformation of the hero’s image under the influence of national literary traditions and historical consciousness.Keywords: heroism, patriotism, spiritual endurance, war prose, Ba Jin, Baurzhan Momyshuly, moral choice, national consciousness, hero image.